PPG Students' Learning Competency Analysis From Self Regulated Learning Factors - Mawardi Mawardi; Henny Dewi Koeswanti (Jurnal Ilmiah Sekolah Dasar, 2021)
The experience of implementing the Teacher Professional Education (PPG) for Elementary School Teacher Program so far shows that the graduation rate for PPG participants has only reached an average of 70% for the entire class. This condition is undoubtedly a reflection material for managers to improve their performance to achieve more optimal results in the future. This study aimed to analyze PPG student competence, student competence, and differences in student competence based on SRL and low. This type of research is descriptive quantitative research with the comparative correlational method. Techniques and instruments used are student competency document analysis techniques and SRL Measurement Instruments. The sample in this study was 34 PPG students. Data analysis techniques used descriptive statistical techniques, linear regression analysis and t-test. The results of the study found that the average student SRL level score reached 88.76; the average competency score of PPG students reached 90.44; the contribution of SRL to student competence is 15.8%; and students who have SRL significantly in their learning competence. It can be said that all student SRL levels can be said to be very high.